Germans and Poles in the Middle Ages
1 online resource.
Keywords: This volume examines mutual ethnic and national perceptions and stereotypes in the Middle Ages by analysing a range of narrative historical sources, such as chronicles, hagiography, and literary material, with a particular focus on the mutual history of Germany and Poland. What sorts of stereotypes and prejudices existed in the Middle Ages, and how widespread were they? Or what other types of differentiating features were considered, and why? The majority of the contributions clearly shows that medieval authors in general displayed only limited interest in the activities of neighbouring lands, and only then when it concerned their own interests - such as matters of conflict, diplomacy, or marriage - while criticism usually focused on individuals, rather than being generalised to bordering regions as a whole. Contributors are Isabelle Chwalka, Jarochna Dąbrowska-Burkhardt, Stephan Flemmig, Sławomir Gawlas, Georg Jostkleigrewe, David Kalhous, Norbert Kersken, Paul Martin Langner, Roman Michałowski, Wojciech Mrozowicz, Piotr Okniński, Andrzej Pleszczyński, Volker Scior, Florian M. Schmid, Marcin Starzyński, Adam Szweda, Kristin Skottki, Grischa Vercamer, and Thomas Wünsch.